2004
DOI: 10.1021/jp037048u
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopy and Photophysics of Lumiflavins and Lumichromes

Abstract: Solvent effects on the spectroscopic properties of lumichromes and lumiflavins are presented. Fluorescence yields for lumiflavins are an order of magnitude larger than those for lumichromes, due to their lower nonradiative rate constants. Solvent effects on the absorption and emission band positions are explained on the basis of hydrogen-bonding interactions. TD-DFT calculations predicted that the lowest energy states are n,π* in the case of lumichromes, but π,π* in the case of the lumiflavins. The overall con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
134
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(152 citation statements)
references
References 39 publications
18
134
0
Order By: Relevance
“…It has been reported that this first band is not much affected by polarity or the hydrogen bond of the solvent. 8,9 The pictures of MOs in Figure 5 may give an insight as to why the first ? * transition (HOMO ?…”
Section: Electronic Spectrum Of Lumiflavinmentioning
confidence: 99%
“…It has been reported that this first band is not much affected by polarity or the hydrogen bond of the solvent. 8,9 The pictures of MOs in Figure 5 may give an insight as to why the first ? * transition (HOMO ?…”
Section: Electronic Spectrum Of Lumiflavinmentioning
confidence: 99%
“…5) 32 as the masking ligand in the competitive binding system, where the well-separated emission wavelength of lumiflavin (λem = 530 nm) 32 compared to alloxazine (λem = 453 nm) is considered to be appropriate although lumiflavin shows the fluorescence to a certain degree (ffl = 0.14). 31 In the absence of lumiflavin, the most significant fluorescence quenching of alloxazine was obtained for A opposite an AP site in the DNA duplexes, but alloxazine also shows the large response to T. In the competitive binding with lumiflavin, the alloxazine binding to T was effectively blocked due to the strong binding of lumiflavin to T opposite the AP site, which results in the decrease in the fluorescence response of alloxazine to T (Fig. 5).…”
Section: Resultsmentioning
confidence: 99%
“…29,30 In addition, Lch shows fluorescence emission with a maximum at 475 nm that is separated from the emission of ATMND (λem = 405 nm), and shows low fluorescence quatum yield (ffl = 0.088). 31 It is thus expected that Lch effectively inhibits ATMND binding to T without interfering with the binding of ATMND to C. Actually, fluorescence signaling of ATMND is less influenced in the presence of Lch. Enhanced base-discrimination efficiency based on competitive binding of ATMND and Lch at the AP site was discussed as a simple and effective approach to develop AP site-binding ligand-based gene analysis suitable for the practical use.…”
Section: Introductionmentioning
confidence: 99%
“…24,25 Furthermore, an aqueous LC solution exhibits a single fluorescence band at 479 nm with the lifetime of 2.7 ns. 26 On the other hand, RFH2 is produced by photochemical protonation of the N(1) and N(5) atoms in RF and subsequent rearrangements of the double bonds of the ring structure, as illustrated in Fig. 1.…”
Section: Effects Of Acetic Acid On Tir Fluorescence Spectra Of Rf At mentioning
confidence: 99%